2022
DOI: 10.1002/mus.27497
|View full text |Cite
|
Sign up to set email alerts
|

Clinical course and outcome of an outpatient clinic population with myasthenia gravis and COVID‐19

Abstract: identify ALS patients who would benefit from inpatient initiation and titration of NIV and avoid unwanted morbidity with prolonged outpatient titration, or more acute decompensation resulting in unwanted intubation or death. Further studies assessing the survival benefit of ambulatory TCO 2 monitoring and rapid initiation of NIV to tolerance with correction of CO 2 are also warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…A more severe form of COVID-19 (hospitalization required) was recorded in approximately one third of our SARS-CoV-2 infected MG patients. These results coincide with data obtained in the Turkish study [ 19 ], but not with the results from the French cohort study where this percentage was nearly twice as high [ 20 ]. The explanation for this dissimilarity may be the fact that 60% of patients in the French study had a severe form of MG at the time of COVID-19 infection, while most of our patients had a mild form of MG.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…A more severe form of COVID-19 (hospitalization required) was recorded in approximately one third of our SARS-CoV-2 infected MG patients. These results coincide with data obtained in the Turkish study [ 19 ], but not with the results from the French cohort study where this percentage was nearly twice as high [ 20 ]. The explanation for this dissimilarity may be the fact that 60% of patients in the French study had a severe form of MG at the time of COVID-19 infection, while most of our patients had a mild form of MG.…”
Section: Discussionsupporting
confidence: 86%
“…Moreover, these data are in accordance with a Polish study where 33.3% of MG patients had COVID-19 [ 18 ]. On the other hand, previous studies from Turkey and France reported significantly lower prevalence of COVID-19 infection (0.96% and 13.5%, respectively) among patients with MG [ 19 , 20 ]. The basic cause of these differences might be the disparity between the study conducting time and the course of the pandemic, as well as different prevalence among general population in these countries.…”
Section: Discussionmentioning
confidence: 76%
“…On the other hand, MG may be triggered or worsened by infections in general [ 24 ]. Small-scale studies have been conducted regarding COVID-19 specifically, showing increased exacerbation rate, need for increased dosage, and prolonged hospital stay following infection [ 25 , 26 ]. A case report has shown a myasthenic crisis as a complication of COVID-19 [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Exacerbation of MG due to COVID-19 has been reported in new-onset pediatric cases 4 and adult cases. 2 5 6 7 8 9 However, to the best of our knowledge, the effect of COVID-19 in children with MG remains unclear.…”
Section: Discussionmentioning
confidence: 99%